The Effect of Greenwashing, Green Word of Mouth, Green Trust and Attitude towards Green Products on Green Purchase Intention - Mayumi Kris Ghassani; Nadhiv Arifata Rahman; Trisha Geraldine; Ina Agustini Murwani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Greenwashing has begun in developing countries, like Indonesia. Enterprises have begun selling their products as "green products" or environment friendly, however this is not totally accurate. This produces concern in the community because it is difficult to believe in a certain brand, whether they truly care about the environment or not. This study aims to determine the correlation between greenwashing, green word of mouth, and attitude towards green products on green purchase intention. Green trust is studied to get a better understanding of attitude. The method used is Theory Reasoned Action (TRA). A sample of 227 participants used the purposive sampling technique. Results were analysed using a PLS-SEM approach. This study showed that greenwashing and attitude towards green product have a positive impact on green purchase intention, while green word of mouth and green trust do not affect green purchase intention. The findings show that greenwashing does not impact green trust, while green word of mouth has a positive impact on green trust. Greenwashing does not impact on attitude towards green products, while green trust and green word of mouth have a positive impact on attitude towards green products. From the data that has been obtained, green marketing method is still effective to increase Indonesia’s customers purchase intention.